The Need for Active Learning is a Concern for Students’ Performance in ELT Context: A Case in Libya Educational School in North Cyprus - Bardis, Ben; Khmis, Suhir Mohamed; Mohamed Krid, Suhir (EduLine: Journal of Education and Learning Innovation, 2024)
The need to enhance language competence of students has become a contemporary issue to tackle in the domain of English Language Teaching (ELT). The fact remains persuasive as teaching and learning approaches must be significant and student-centred in order to enhance students’ language competence in teaching industries. Active learning involves evidence- based teaching tasks to make students take part massively and directly in classroom activities. The purpose of the study is to explore the perception of both the teaching staff and the school managers on the dynamics of active learning. The participants of the study are 10 teachers (6 Females and 4 Males) and 3 Managers in Secondary School Section of Libyan Educational School in North Cyprus. The investigation entails a qualitative method by using interview guide questions for both the EFL teaching staff and school managers. The study’s findings indicate that, though the teachers and their managers are aware of active learning, they however lack logistics to implement and sustain its policies. The pedagogical implication stresses on the following strategical issues such as Fundamental strategy; Emphasis on positive learning styles; Reassurance for student-student’s interactive communication and Making students innovators and self-sufficient in learning. Furthermore, these strategic tasks serve as a take-home knowledge to engross our students in active learning for the enhancement of the four language skills in English as a foreign language (EFL) context.